2016
DOI: 10.1016/j.jcol.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel and oxidative stress changes in an experimental model of portal hypertension: action of N-acetylcysteine

Abstract: Introduction Portal hypertension (PH) is characterized by vasodilatation in the portal system and the bowel is one of the severely affected organs. N-acetylcysteine (NAC) is a molecule with important properties and widely used in clinical practice. Objective To evaluate NAC action in the bowel of animals submitted to the animal model of partial portal vein ligation (PPVL). Methods 18 male Wistar rats were divided into three experimental groups (n = 6): sham-operated (SO), PPVL, and PPVL + N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…From this finding, we can highlight the hypotensive effect on blood pressure since previous studies have demonstrated that NAC can decrease blood pressure values 32,33 . However, further studies are needed to confirm this idea.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…From this finding, we can highlight the hypotensive effect on blood pressure since previous studies have demonstrated that NAC can decrease blood pressure values 32,33 . However, further studies are needed to confirm this idea.…”
Section: Discussionsupporting
confidence: 54%
“…Regarding NAC, despite being considered an antioxidant, it can also be considered as an antidote to poisoning, especially in the liver 29,30 . Other authors highlight its anti-inflammatory properties, including as a means of use against diseases 31,32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation